The Animal Rights Struggle - Traïni, Christophe Traïni (Amsterdam University Press, 2015)
From the beginning of the 19th century to the present day, a host of campaigners have denounced the mistreatment of animals. Relying on a comparison between the British and French experiences, the present work retraces the various strands of the animal protection movement, from their origins to their continuing impact on current debates. Inextricably linked to the rise of philanthropy, and well established long before the birth of the ecology movement, the story of the collective mobilizations behind the struggle for animal rights sheds light on several crucial processes in our social and political history: changes in sensibilities and socially approved emotions; the definition of what constitutes legitimate violence; the establishment of norms designed to change what constitutes morally acceptable practices; rivalry between elites having differing conceptions of the forms authority should take; the influence of religious belief on militant activities; and the effects of gender discrimination.